2012
DOI: 10.1142/s0217732312300340
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Large Galactic Disks Through the Hierarchical Scenario: Further Consequences

Abstract: Using the deepest and most complete observations of distant galaxies, we investigate the progenitors of present-day large spirals. Observations include spatially-resolved kinematics, detailed morphologies and photometry from UV to mid-IR. Six billions years ago, half of the present-day spirals were starbursts experiencing major mergers, evidence for this is provided by their anomalous kinematics and morphologies. They are consequently modeled using hydrodynamics models of mergers and it perfectly matches with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…In fact, the merger model of M31 of Hammer et al (2010) predicted the disk of satellites discovered by Ibata et al (2013). Spatial locations of these M31 satellites are drawing two loop systems (see Figure 3d and Hammer et al 2013) similar to those found around NGC5907, i.e., typical signatures of ancient major mergers.…”
Section: Relics Of Ancient Mergers In the Nearby Universementioning
confidence: 54%
See 4 more Smart Citations
“…In fact, the merger model of M31 of Hammer et al (2010) predicted the disk of satellites discovered by Ibata et al (2013). Spatial locations of these M31 satellites are drawing two loop systems (see Figure 3d and Hammer et al 2013) similar to those found around NGC5907, i.e., typical signatures of ancient major mergers.…”
Section: Relics Of Ancient Mergers In the Nearby Universementioning
confidence: 54%
“…The later provides a robust explanation of the stellar Giant Stream, which could be made of tidal tail stars captured by the galaxy gravitational potential of the stellar loops, 5.3 Gyrs after a 3:1 merger (first passage, 6.8 Gyrs ago, f initial gas =60%, f initial baryons =17%, see Wang et al 2012). (c): Stellar particles associated to an ancient 3:1 merger at M31 location (GADGET2, 8M particles see Hammer et al 2010Hammer et al , 2013Fouquet et al 2012), and forming a plane seen almost edge-on, coinciding with the observed satellite plane (almost seen edge-on, in blue color) found by Ibata et al (2013). (d): Same as (c) but rotated by 90 degrees to reveal the loops system in the loop plane.…”
Section: Relics Of Ancient Mergers In the Nearby Universementioning
confidence: 68%
See 3 more Smart Citations